Effects of candy and chewing gum on reduction of motion sickness - TOKUMOTO, Takumi; SUZUKI, Kaoru; GOTO, Takeshi; TAKIGUCHI, Toshio (Ningen kogaku. The Japanese journal of ergonomics, 2001)
The effects of chewing gum or tasting candy on the reduction of motion sickness were examined by subjecting 97 subjects (in total) to 40 minutes of sway on a motion base. The experimental conditions were chewing gum, tasting candy, and none. A comparison of subjective evaluations showed that chewing gum or tasting candy tended to reduce subjective motion sickness. Furthermore, a comparison of the area of the center of gravity before and after the sway showed that the experimental condition of chewing gum indicated the least increase. The condition without gum or candy indicated the greatest increase. The results implied that chewing gum or tasking candy had reduced motion sickness, and that the effect was both subjective and objective.